IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 3 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK: STUDI KASUS KECAMATAN TEMBALANG - Arifin Setyan Cahyanto; Wahid Abdulrahman; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
Semarang City as one of the autonomous regions, has actually implemented the law by establishing non-smoking areas through Mayor Regulation No. 12 of 2009 on Non-Smoking Area and Limited Area of Smoking. With the aim of reinstating the zoning of the area without smoking and its management so that public health can be protected and improved from the disruption of cigarette smoke. This study aims to find out how the implementation of Regional Regulation No. 3 of 2013 on Non-Smoking Areas in health care facilities, teaching and learning process, and government offices in Tembalang Sub-district Semarang.Dan also know what are the factors inhibiting the performance apparatus in service facilities health, teaching and learning process, and government offices in Tembalang Sub-district, Semarang City, in the implementation of Perda Non-Cigarette Regions.The method used in this study using descriptive qualitative. The subject of this research is the government that is represented by the Health Office of Semarang City, responsible for the implementation of the policy, and the community. The sampling technique used in this research is Proportionate Stratified Random Sampling. The analysis used is qualitative analysis.Based on the result of research which can be concluded: 1) Implementation of Local Regulation Number 3 Year 2013 about Non Smoking Area in health service facility, teaching and learning place, and government office in Tembalang Sub-district Semarang not optimal yet 2) Factors that hamper apparatus performance in health facility , where the teaching and learning process, and government offices in District Tembalang Semarang City in the implementation of the Regional Regulation No Smoking, among others, communication, disposition and behavior change. Keywords: Implementation, Regional Regulation, Non-Smoking Area